2000
DOI: 10.1074/jbc.m001706200
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Characterization, and Crystal Structure of the Omega Class Glutathione Transferases

Abstract: A new class of glutathione transferases has been discovered by analysis of the expressed sequence tag data base and sequence alignment. Glutathione S-transferases (GSTs) of the new class, named Omega, exist in several mammalian species and Caenorhabditis elegans. In humans, GSTO 1-1 is expressed in most tissues and exhibits glutathione-dependent thiol transferase and dehydroascorbate reductase activities characteristic of the glutaredoxins. The structure of GSTO 1-1 has been determined at 2.0-Å resolution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
647
2
12

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 657 publications
(681 citation statements)
references
References 59 publications
15
647
2
12
Order By: Relevance
“…Among the Australian, African and Chinese populations, GSTO1*A was the most prevalent haplotype with a frequency ranging from 0.6 to 0.9; whereas GSTO1*B*A was the least common, with a frequency of 0.01-0.05 (Whitbread et al, 2003). GSTO1*A demonstrated a GSH-dependent reduction of dehydroascorbate, a function characteristic of glutaredoxins rather than GSTs (Board et al, 2000). This allele was first described as the human monomethylarsenic acid reductase, (MMA[V]), and is the rate-limiting enzyme of inorganic arsenic metabolism (Zakharyan et al, 2001).…”
Section: Omega Classmentioning
confidence: 98%
See 3 more Smart Citations
“…Among the Australian, African and Chinese populations, GSTO1*A was the most prevalent haplotype with a frequency ranging from 0.6 to 0.9; whereas GSTO1*B*A was the least common, with a frequency of 0.01-0.05 (Whitbread et al, 2003). GSTO1*A demonstrated a GSH-dependent reduction of dehydroascorbate, a function characteristic of glutaredoxins rather than GSTs (Board et al, 2000). This allele was first described as the human monomethylarsenic acid reductase, (MMA[V]), and is the rate-limiting enzyme of inorganic arsenic metabolism (Zakharyan et al, 2001).…”
Section: Omega Classmentioning
confidence: 98%
“…First, X-ray crystallography shows a unique 19-residue N-terminus extension that forms a structural unit quite unlike any found in other classes. At present, its function remains undefined (Board et al, 2000). Second, known substrates of other GSTs are not catalysed by GSTO.…”
Section: Omega Classmentioning
confidence: 99%
See 2 more Smart Citations
“…GSTO1 (glutathione transferase omega 1) is a member of the glutathione S-transferase (GST) family of phase II enzymes that catalyze glutathione-dependent detoxification. 32 The role of GST has been evaluated in drug resistance. Schisselbauer et al 33 reported that an elevated GST level in tumors was detected after the development of clinical drug resistance.…”
Section: Characterization Of Tzt-1027 In Reference Profilingmentioning
confidence: 99%